Classification of the external auditory canal cholesteatoma - Naim, Ramin; Linthicum, Fred; Shen, Ted; Bran, Gregor M.; Hörmann, Karl (The laryngoscope, 2005)
Objectives/Hypothesis: The external auditory canal cholesteatoma (EACC) is a rare disease in the field of otolaryngology. Only 1 in 1,000 new otologic patients present with this entity, which was first described by Toynbee. The aim of this article is to classify EACC by different histopathologic and clinical findings of patients presenting to the Department of Otolaryngology at the University of Mannheim, Germany. Methods: From 2000 to 2004, 17 patients presented to our clinic with EACC. The cholesteatoma were treated surgically, and the specimens were investigated histologically. Clinical findings were also recorded. We classified four stages: stage I with hyperplasia of the canal epithelium, stage II including periosteitis, Stage III including a defective bony canal, and stage IV showing an erosion of adjacent anatomic structure. Results: Eight patients presented with stage II, five patients with stage III, three with stage I, and only one patient presented with erosion of the mastoid cells, which was determined as stage IV. Conclusion: In summary, our classification serves to describe the different histopathologic and clinical stages of EACC.